2011
DOI: 10.1111/j.1440-1754.2011.02077.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory problems in children with Down syndrome

Abstract: Down syndrome is associated with a significant health burden, which is particularly apparent in young children who will frequently present with cardiac and respiratory problems. Respiratory presentations include problems related to structural abnormalities of the airways and lungs, glue ears, recurrent lower respiratory tract infections and obstructive sleep apnoea. These conditions are readily identifiable and able to be treated. An awareness of the breadth of respiratory problems and a plan to monitor patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 49 publications
2
64
0
10
Order By: Relevance
“…As infecções respiratórias agudas em geral representam um grande espectro, incluindo rinofaringites, sinusites, otites e pneumonias [3]. Essas enfermidades podem ter diferentes agentes etiológicos, principalmente vírus e bactérias, e são mais frequentes em crianças com SD [5].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…As infecções respiratórias agudas em geral representam um grande espectro, incluindo rinofaringites, sinusites, otites e pneumonias [3]. Essas enfermidades podem ter diferentes agentes etiológicos, principalmente vírus e bactérias, e são mais frequentes em crianças com SD [5].…”
Section: Discussionunclassified
“…Além de diferentes conformações nas vias aéreas superiores, pessoas com SD apresentam alterações morfológicas das vias aéreas inferiores e do parênquima pulmonar [16], que também podem contribuir para a maior suscetibilidade a infecções. Ainda existe um baixo índice de sucesso ao se utilizarem os instrumentos de avaliação da função pulmonar em crianças com SD, o que dificulta o entendimento e o esclarecimento do papel dessas alterações morfofuncionais [3]. Por outro lado, muitos estudos têm sugerido uma importante interferência dos fatores imunológicos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In addition, gastroesophageal reflux, immunologic dysfunction, tracheal bronchus, airway malacia, CHD, and pulmonary hypoplasia cause recurrent lower airway diseases. 11 Cooney and Thurlbeck showed that 6 of 7 patients with DS had hypoplastic lungs, and 5 had CHD. 12 Patients with DS have a decreased number of alveoli in relation to acini, enlarged alveoli and alveolar ducts, and a smaller alveolar surface area, which can lead to exacerbation of pulmonary hypertension in DS.…”
mentioning
confidence: 99%
“…Pandit et al suggest there are many respiratory problems in both the upper and lower airways of children with DS. 11 Anatomic characteristics in DS such as large tongue, small hypopharynx, pharyngeal hypotonia, tonsils and adenoid enlargement, laryngomalacia, and tracheomalacia cause upper airway problems. In addition, gastroesophageal reflux, immunologic dysfunction, tracheal bronchus, airway malacia, CHD, and pulmonary hypoplasia cause recurrent lower airway diseases.…”
mentioning
confidence: 99%